The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/app11167766
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Fuzzy System Oriented toward High-Dimensional Data and Interpretable Artificial Intelligence

Abstract: Fuzzy systems (FSs) are popular and interpretable machine learning methods, represented by the adaptive neuro-fuzzy inference system (ANFIS). However, they have difficulty dealing with high-dimensional data due to the curse of dimensionality. To effectively handle high-dimensional data and ensure optimal performance, this paper presents a deep neural fuzzy system (DNFS) based on the subtractive clustering-based ANFIS (SC-ANFIS). Inspired by deep learning, the SC-ANFIS is proposed and adopted as a submodule to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Therefore, this combination was chosen to be our parameter sharing strategy in the following experiments. Compared HI-FCMDPL-CP1 with HI-FCMDPL-CP2, we can conclude that PS improved the classification performance [36], [37] regardless of whether MIC and RI were used or not.…”
Section: ) the Effect Of Parameter Sharing And Non-parameter Sharingmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, this combination was chosen to be our parameter sharing strategy in the following experiments. Compared HI-FCMDPL-CP1 with HI-FCMDPL-CP2, we can conclude that PS improved the classification performance [36], [37] regardless of whether MIC and RI were used or not.…”
Section: ) the Effect Of Parameter Sharing And Non-parameter Sharingmentioning
confidence: 90%
“…Though cascaded fuzzy system (CFS) and cascaded centralized TSK fuzzy system (CCTSKFS) has obvious superiority over the conventional FSs in approximation accuracy, robustness and interpretability [34], there are still problems such as rule explosion, poor interpretability and complex structure [35]. Our recently research in [36], [37] showed that parameter sharing (PS) and random input (RI) outperformed ANFIS in training Takagi-Sugeuo-Kang (TSK) fuzzy regression models. So, PS and RI are still used in our proposed approach.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research in Chen et al 50 shows that the ways of feature input have a significant impact on algorithm performance. The SOTA methods (i.e., DCFS, 48 iDCFS 51 ) utilized the whole feature space of the data to construct their models, leading to lengthy rules for high-dimensional data and degradation of interpretability.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are all generated based on the initial global model (and hence in series with the global model), and then, the model to be used is identified. Compared with existing approaches, 50,54 the new approach involves (1) an improved PL (iPL) is developed by fuzzy c-means (FCM) clustering 55 to significantly decrease the fuzzy rules and computational load; (2) two hierarchical (deeper-learned) iPL FSs are constructed; (3) The iPL is enhanced in DPLFSs by replacing the shared membership functions (MFs) with independent ones in adaptive network-based fuzzy inference system (ANFIS), and hence to decouple the number of rules from the number of MFs in each input domain, and (4) PL only considered low dimensional in 1D/2D/3D regression problems, PL is extended to high dimensional space in this paper; (5) PCC, MIC and principal components analysis (PCA) are adopted as an automated feature extraction algorithm to optimize deep DPLFSs.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to use training algorithms with neural networks when representing the fuzzy system as a neural network that grants higher accuracy in the fuzzy system performance. When representing a fuzzy system as a neural network, a neuro-fuzzy system is obtained [4,5].…”
Section: Introductionmentioning
confidence: 99%